Postmodernism : style and subversion, 1970-1990 - Adamson, Glenn; Pavitt, Jane.; Antonelli, Paola; Victoria and Albert Museum (London : V&A Pub. ; New York : Distributed in North America by Harry N. Abrams Inc., 2011)
The radical ideas associated with postmodernism swept through the arts in the 1970s, but have always been hard to summarise. This book presents the movement as not merely an aesthetic vocabulary, but also as a subversive attitude - a new way of looking at the world.
Postmodernism : style and subversion / Glenn Adamson and Jane Pavitt -- Arch-art : architecture as subject matter / James Wines -- Our postmodernism / Denise Scott Brown -- On bricolage / Victor Buchli -- Kitsch and postmodern architecture : Charles Moore's Piazza d'Italia / Patricia A. Morton -- Irony and postmodern architecture / Emmanuel Petit -- Civitas Interruptus / Thomas Wea
"Published to accompany the exhibition ... at Victoria and Albert Museum, London, 24 September 2011 - 15 January 2012"--T.p. verso.
Includes bibliographical references (p. 289-303) and index.
Keywords: Postmodernism -- Exhibitions; Arts, Modern -- 20th century -- Exhibitions; Postmoderne; Ausstellung -- London -- 2011.